Peran Mahasiswa dalam menerapkan Model Pembelajaran Melalui Program PLP di SMA Negeri 8 Palembang - Amelia Azahra; Made Deliayana Anggreni; Risma Dwiyanti; Siti Aisa; Desi Irliani; Henna Henna; Lora Sepitra; Cahaya Renata; Rahmalia Tri Utami; Faradiva Lee; Rahman Rahman; Nyoman Puja; Reviska Amarba; Adelia Azzahara; Rini Seltia (Lembaga Pengembangan Kinerja Dosen, 2026)
The School Field Introduction Program (PLP) is an activity that provides students as prospective teachers with real experience in understanding and implementing the learning process at school. This research aims to determine the role of students in implementing the learning model through the PLP program at SMA Negeri 8 Palembang. The method used is descriptive qualitative with data collection techniques in the form of observation, documentation and direct teaching practice. The results of implementing PLP show that students play an active role in designing and implementing learning models, such as Problem Based Learning (PBL), group discussions and presentations. The application of this model can increase students' activeness, participation and critical thinking abilities during learning. In addition, students gain experience in managing classes, compiling learning tools, and adapting to the characteristics of diverse students. The PLP program also makes a positive contribution to the development of students' pedagogical, professional, social and personality competencies as prospective educators. Thus, PLP becomes an effective means of preparing students to become professional and competent teachers.